Pengaruh Love of Money, Gaya Hidup Hedonismee, dan Locus of Control terhadap Perilaku Keuangan Mahasiswa: Studi Kasus: Mahasiswa Fakultas Ekonomi Universitas Islam Kadiri - Suci Dwi Prasetiyo; Edwin Agus Buniarto; Nurali Agus Najibul Zamzam (JURNAL RISET MANAJEMEN (JURMA), 2026)
This study aims to analyze the influence of love of money, hedonistic lifestyle, and locus of control on the financial behavior of students at the Faculty of Economics, Kadiri Islamic University. The background of this research is based on the low level of saving awareness and the tendency toward consumptive behavior among students, which are influenced by psychological factors and lifestyle. This study employed a quantitative approach using a survey method. The population consisted of students from the Faculty of Economics at Kadiri Islamic University, with samples selected using a simple random sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression analysis.The results showed that partially, love of money, hedonistic lifestyle, and locus of control had a significant effect on students’ financial behavior. A hedonistic lifestyle tended to have a negative effect on financial behavior, while locus of control had a positive effect in improving financial management abilities. Simultaneously, the three variables significantly influenced students’ financial behavior.This research is expected to contribute to the development of financial management knowledge, particularly regarding students’ financial behavior, and to serve as a consideration for students in managing their finances more wisely.